2015
DOI: 10.11646/zootaxa.3962.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of shovel-jaw carp Onychostoma (Teleostei: Cyprinidae) from southern Vietnam

Abstract: Two new species of large shovel-jaw carps in the genus Onychostoma are described from the upper Krong No and middle Dong Nai drainages of the Langbiang Plateau in southern Vietnam. These new species are known from streams in montane mixed pine and evergreen forests between 140 and 1112 m. Their populations are isolated in the headwaters of the upper Sre Pok River of the Mekong basin and in the middle of the Dong Nai basin. Both species are differentiated from their congeners by a combination of the following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The present study strongly supported that some species of Acrossocheilus, Onychostoma and F. brevifilis belong to the monophyletic group (Clade III), including A. monticola, A. yunnanensis, O. rarum, O. alticorpus and F. brevifilis. Interestingly, our results corroborate the previous finding that O. rarum is the sister group of O. alticorpus (Hoang et al 2015;Song et al 2018;Zhang et al 2018), but Zhai et al (2020) suggested that O. rarum appeared to be more closely related with O. barbatulum and O. barbatum. We suggested that the specimens of O. rarum (NC022869.1) were also misidentified.…”
Section: Molecular Phylogeny Of Onychostomasupporting
confidence: 92%
“…The present study strongly supported that some species of Acrossocheilus, Onychostoma and F. brevifilis belong to the monophyletic group (Clade III), including A. monticola, A. yunnanensis, O. rarum, O. alticorpus and F. brevifilis. Interestingly, our results corroborate the previous finding that O. rarum is the sister group of O. alticorpus (Hoang et al 2015;Song et al 2018;Zhang et al 2018), but Zhai et al (2020) suggested that O. rarum appeared to be more closely related with O. barbatulum and O. barbatum. We suggested that the specimens of O. rarum (NC022869.1) were also misidentified.…”
Section: Molecular Phylogeny Of Onychostomasupporting
confidence: 92%
“…Additionally, a rich diversity in bats has also been documented in the region [15]. In the recent decade, several new vertebrates including six fishes [16,17], three snakes [18][19][20], and four amphibians [21][22][23][24] were described from the Langbiang Plateau. Across the plateau, cryptic genetic diversity was also detected in the frog genus Leptolalax [25].…”
Section: Plos Onementioning
confidence: 99%